Temptation transformed: the story of how the forbidden fruit became an apple - Yadin-Israel, Azzan (University of Chicago Press, 2023)
Intro -- Contents -- List of Illustrations -- Introduction: The Curious Case of the Apple -- 1. The Missing Apple -- 2. A Bad Latin Apple -- 3. The Iconographic Apple -- 4. The Vernacular Apple -- Conclusion: A Scholarly Reflection -- Acknowledgments -- Appendix: Inventory of Fall of Man Scenes -- Early Christian, Byzantine, and Carolingian -- France before 1250 -- France after 1250 -- Germany, England, and the Low Countries before 1250 -- Germany, England, and the Low Countries after 1250 -- Italy and Spain before 1250 -- Italy and Spain after 1250 -- Abbreviations -- Notes -- Bibliography -- Index -- Color plates.